+0  
 
0
281
1
avatar

3 times the sqrt of 6 ( 5 times the sqrt of 2 )

Guest Apr 10, 2017
 #1
avatar+92856 
+3

3√6   *  5√2   =

 

3 *   5   *  √6   * √2  =

 

15 * √12   =

 

15 * √4 *  √3  =

 

15 * 2 * √3  =

 

30√3

 

 

cool cool cool

CPhill  Apr 10, 2017

9 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.